Hyperthermia-Induced Changes in EEG of Anesthetized Mice Subjected to Passive Heat Exposure - de Labra, Carmen; Pardo-Vazquez, Jose L.; Cudeiro, Javier; Rivadulla, Casto (Frontiers in Systems Neuroscience, 2021)
Currently, the role of hypothermia in electroencephalography (EEG) is well established. However, few studies have investigated the effect of hyperthermia on EEG, an important physiological parameter governing brain function. The aim of this work was to determine how neuronal activity in anesthetized mice is affected when the temperature rise above the physiological threshold mandatory to maintain the normal body functions. In this study, a temperature-elevation protocol, from 37 ºC to 42 ºC, was applied to four female mice of 2-3 months old while EEG was recorded simultaneously. We found that hyperthermia reduces EEG amplitude by 4.36% when rising from 37 to 38 degrees and by 24.33% when it is increased to 42 degrees. Likewise, increasing the body temperature produces a very large impact on the EEG spectral parameters, reducing the frequency power at the theta, alpha, and beta bands. Our results show that hyperthermia has a global effect on the EEG, being able to change the electrical activity of the brain.